Upaya Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Sub Bahasan Perilaku Percaya Diri, Tekun dan Hemat Melalui Strategi Pembelajaran Example Non Example di Kelas III SD Negeri 22 Pulasan Kec. Tanjung Gadang - Kamidar (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2020)
Based on the experience of researchers at SDN 22 Pulasan in class III PAI subjects, information was obtained that KKM was an Islamic Education subject. From the KKM 75 that was determined, among the third grade students of SDN 22 Pulasan, only reaching the KKM in these subjects was still less than the KKM 75% which ultimately caused the teacher to make remedials. This shows that the learning outcomes achieved by students are still low. This type of research is Classroom Action Research (PTK) or a translation of Classroom Action Research. Classroom Action Research is action research carried out in the classroom when learning takes place. This research was conducted with the aim of improving or improving the quality of learning. This research also focuses on class or on the learning process that occurs in the classroom. Based on the results of research in cycle I and cycle II after the implementation of the Example non Example learning strategy, it can improve student learning outcomes in the subject of Islamic Religious Education on the subject of Confidence, Perseverance and Thrifty Behavior in class III SDN 22 Pulasan This can be proven by the increased learning outcomes of students after the implementation of the Example non Example learning strategy. In the pre-cycle stage there was an average of 57.94 with 52% classical completeness, in the first cycle the average learning outcomes were 71.47 with classical completeness reaching 70%. And in cycle 2 the average learning outcomes are 83.23 with classical completeness reaching 88%.